21ST CENTURY SKILLS LEARNING USING LEMMANG LEARNING RESOURCES: A STUDY OF ETHNOMATHEMATICAL BUGIS MAKASSAR - Tampa, Alimuddin; Firdaus, Andi Mulawakkan; Ja’faruddin, Ja’faruddin; Chen, Wen-Haw (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
Abstract: 21st century learning demands the application of skills and knowledge that are relevant to everyday life. While mathematics is a subject taught at all levels of education, it remains challenging for many students. Often perceived as disconnected from culture, students may find learning mathematics less meaningful. This perception is partly due to the lack of integration between mathematics education in schools and cultural context. However, mathematics is inherently connected to culture, and one approach recognizing this connection is called ethnomathematics. This approach emphasizes a culture-based learning process, and has the potential to improve students' learning outcomes. One example of how culture can be used as a source of mathematics learning is through the study of the traditional food of the Bugis-Makassar ethnic heritage called "lemmang". The process of making lemmang involves mathematical creativity, and researchers have used a descriptive qualitative research method with an ethnographic approach to explore this creativity. This involved collecting data through interviews, observation, and documentation. The research results showed that in lemmang making process, there is mathematical creativity related to the concepts of division, cylinder, and the principles of the Pythagorean theorem. This demonstrates that culture can be a valuable source of mathematics learning for teachers and students. Abstrak: Pembelajaran abad 21 menuntut penerapan keterampilan dan pengetahuan yang relevan dalam kehidupsn sehari-hari. Matematika adalah mata pelajaran yang diajarkan di semua tingkat pendidikan, tetapi tetap menjadi tantangan bagi banyak siswa. Mereka sering memandang matematika sebagai mata pelajaran yang terputus dari budaya dan kurang bermakna. Hal ini disebabkan karena pendidikan matematika di sekolah belum mengintegrasikan mata pelajaran dengan budaya. Matematika secara inheren terhubung dengan budaya, dan satu pendekatan yang mengakui hubungan ini disebut etnomatematika. Pendekatan ini menekankan proses pembelajaran berbasis budaya, dan berpotensi meningkatkan hasil belajar siswa. Salah satu contoh bagaimana budaya dapat dijadikan sebagai sumber pembelajaran matematika adalah melalui pembelajaran tentang makanan tradisional peninggalan etnis Bugis-Makassar yang disebut lemmang. Proses pembuatan lemmang melibatkan kreativitas matematis, dan peneliti telah menggunakan metode penelitian kualitatif deskriptif dengan pendekatan etnografi untuk menggali kreativitas tersebut. Pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa dalam proses pembuatan lemmang terdapat kreativitas matematika yang berkaitan dengan konsep pembagian, silinder, dan prinsip teorema Pythagoras. Hal ini menunjukkan bahwa budaya dapat menjadi sumber pembelajaran matematika yang berharga bagi guru dan siswa.